PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUASAN PELANGGAN PADA PRODUK PT DUA KELINCI DI BANJARMASIN - rika sylvia; Penta lestarini budiati; Eka Syafitri (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2021)
The purpose of this study was to determine the effect of product quality and price on customer satisfaction at PT Dua Kelinci products in Banjarmasin either partially or simultaneously. The type of research used is descriptive quantitative. The population in this study were customers of PT Dua Kelinci's products in Banjarmasin with a total sample of 86 customers. Analysis of the data in the study using multiple linear regression method with the help of SPSS version 22.0 application. The results of this study based on multiple linear regression analysis Y = -0.334 + 0.174X1 + 0.398X2, that the product quality and price variables have a positive influence on customer satisfaction at PT Dua Kelinci products in Banjarmasin. The results of the t-test calculation, which says there is a partially significant effect of product quality components (X1) and price (X2) on customer satisfaction of PT Dua Kelinci's products in Banjarmasin (Y). The results of the F test calculation, there is a simultaneous significant effect between product quality (X1) and price (X2) on customer satisfaction of PT Dua Kelinci's products in Banjarmasin (Y). The value of the coefficient of determination (R2) produced is 0.664. This means that 66.4% changes in the customer satisfaction variable for PT Dua Kelinci's products in Banjarmasin (Y) can be explained by changes in product quality (X1) and price (X2) variables, while the remaining 33.6% is explained by other variables not included in the study.